Implementasi Kepatuhan Syariah dalam Pengelolaan Hotel Syariah: Studi Wawancara terhadap Manajer dan Konsultan Industri - Siti Nur Husna Abd Rahman; Rafidah Mohd Azli; Nursafra Mohd Zhaffar; Siti Nadiah Binti Babge (Economia: Journal of Economics and Management, 2026)
The Islamic hospitality industry has experienced rapid growth over the past decade, in line with the expansion of global halal tourism. However, the practice of Shariah compliance among Shariah-compliant hotels continues to face challenges, particularly in terms of policy implementation, monitoring, and standardisation. This study aims to explore Shariah compliance practices in the management of Shariah-compliant hotels in Malaysia using a qualitative approach. Data were collected through semi-structured interviews involving hotel managers and industry consultants with extensive experience in operational management and Shariah-related aspects. Thematic analysis was employed to analyse the collected data. The findings reveal three main themes in Shariah compliance practices: (1) the implementation of Shariah policies and guidelines, (2) human resource and training challenges, and (3) the need for continuous monitoring and auditing. The study also identifies the need for comprehensive Shariah standard operating procedures (SOPs) as well as technological support to ensure consistent compliance monitoring. This research contributes to the existing literature on Islamic hotel management and provides practical guidance for hotel management and relevant authorities in enhancing a more effective and sustainable Shariah compliance system. Abstrak Industri perhotelan Islam mengalami pertumbuhan pesat dalam dekade terakhir, seiring dengan perkembangan pariwisata halal global. Namun, praktik kepatuhan syariah di kalangan hotel syariah masih menghadapi berbagai tantangan, khususnya dalam aspek implementasi kebijakan, pemantauan, dan standardisasi. Penelitian ini bertujuan untuk mengeksplorasi praktik kepatuhan syariah dalam pengelolaan hotel syariah di Malaysia melalui pendekatan kualitatif. Data dikumpulkan melalui wawancara semi-terstruktur yang melibatkan manajer hotel dan konsultan industri yang berpengalaman dalam manajemen operasional serta aspek-aspek kesyariahan. Analisis tematik digunakan untuk mengkaji data yang diperoleh. Hasil penelitian menunjukkan adanya tiga tema utama dalam praktik kepatuhan syariah, yaitu: (1) implementasi kebijakan dan pedoman syariah, (2) tantangan sumber daya manusia dan pelatihan, serta (3) kebutuhan akan pemantauan dan audit berkelanjutan. Penelitian ini juga mengidentifikasi perlunya standar operasional prosedur (SOP) syariah yang komprehensif serta dukungan teknologi untuk memastikan pemantauan kepatuhan yang konsisten. Studi ini berkontribusi terhadap literatur yang ada dalam bidang pengelolaan hotel Islam dan memberikan panduan praktis bagi manajemen hotel serta otoritas terkait dalam meningkatkan sistem kepatuhan syariah yang lebih efektif dan berkelanjutan.